Makanan Tumpeng dalam Tradisi Bancakan - M. Zein Ed-Dally; Nur Faizah (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2020)
Abstract: The lack of culinary treasures in our historical literature is the background of this research. Therefore, this study aims to find out the history and philosophy of Tumpeng in the tradition of pre-Islamic Javanese society and to understand the development of Tumpeng in the bancakan tradition of Javanese society after the arrival of Islamic influence. This study uses historical (historical) research methods which include heuristic methods, source verification, text interpretation, and historiography, as well as using a gastronomic approach. Apart from that, this study also uses the theory of symbolic culture based on Clifford Geertz's version as a tool for historical analysis. The results of this study found several historical facts, namely: 1) Tumpeng is a food that has existed since the Javanese people still embraced the Kapitayan belief, which is served and offered as a means to worship